Automatic Enrollment, Employer Match Rates and Employee Compensation in 401(k) Plans - Barbara A. Butrica; Nadia S Karamcheva (Institute for the Study of Labor (IZA), 2015)
This study uses restricted-access employer-level microdata from the National Compensation Survey to examine the relationship between automatic enrollment and employee compensation. By boosting plan participation, automatic enrollment has the potential to increase employer defined contribution plan costs as previously unenrolled workers receive matching contributions. Using cross-sectional variation in employer compensation costs and the automatic enrollment provision within firms sponsoring DC plans, we examine differences in compensation between those with and without the provision. A significant negative correlation exists between the generosity of the employer match structure and the automatic enrollment provision. However, we find no evidence that total compensation costs or DC costs differ between firms with and without automatic enrollment, and no evidence that DC costs crowd out other forms of compensation.
Keywords: J26; J31; J32; 330; automatic enrollment; defined contribution plan costs; employer match generosity; employee wage and non-wage compensation; firm behavior